Optimize flow layout and analysis of effectiveness at bi technologies Corporation Sdn. Bhd - Nur Afiqah, Noor Azman (2013)
Agilent Production cell 6 fosters inefficient production practices, is outdated for its existing process, and lacking in product flow. A plant optimization is applied to bring order, efficiency, and optimize flow in the production lines. Deliverables include a proposed process and material flow that decreases product travel distances, cross flow and increases productivity as well as effectiveness of the proposed optimization analysis. Major modification of the cell decisions include downsizing the existing cell, sorting to find waste in material handling and establishing a clear process/product flows. The proposed plant optimization was analysis and results yield 100% productivity. The percentage efficiency of the optimize flow layout is 80% compared to 67% in existing flow layout. The analysis of efficiency has been increased to 13% in the proposed process flow. The product travel distance also has been reduced from 93 feet’s to 20 feet’s.